Peran Hakim dalam Sengketa Tanah Berbasis Hukum Perdata: Analisis terhadap Kesenjangan Putusan Pengadilan - Muthallib, Abdul (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2024)
Ideally, in resolving land disputes based on civil law, judges are expected to deliver fair, consistent decisions grounded in objective legal reasoning. However, in reality, there is often a gap in judicial decisions that reflects inconsistencies in the application of the law, which can lead to injustice for the parties involved in the dispute. This study aims to analyze the role of judges in land disputes based on civil law and identify the factors contributing to discrepancies in judicial decisions. The research methodology used is normative legal research, with data sources including legislation and relevant land dispute cases. The research concludes that the role of judges in land disputes is crucial for delivering justice, but it is often influenced by inconsistencies in the application of the law. Therefore, continuous training for judges, the development of more detailed technical guidelines, and strengthening the land information system that is accessible transparently to all relevant parties are necessary.